EFFECT OF THE BROMIDE IONS ON THE TITANIUM ELECTRODE DISSOLUTION POLARIZED BY ALTERNATING CURRENT IN AQUEOUS SOLUTIONS - A.B. Bayeshov; R.N. Nurdillayeva; Sh.H. Khabibullayeva (Academic Scientific Journal of Chemistry, 2019)
The titanium electrode dissolution possibility polarized by industrial alternating current (AC) with 50 Hz frequency in potassium bromide aqueous solution acidified by sulfuric acid was shown for the first time and the process dissolving titanium were determined. The influence of alternating current density (200-1200 A/m2 ), potassium bromide solution concentration (1.0-5.0 M) and sulfuric acid concentration (0.5-4.0 M), AC frequency (25-150 Hz), electrolyte temperature (25-80°C) and electrolysis duration (0.5-2 hours) on the current efficiency (CE) of the titanium dissolution were considered. It was observed extremely low CE (1.8%) of the titanium dissolution by polarization anodic direct current. When titanium was polarized by alternating current, the CE reached 60% at a current density of 200 A/m2 in the titanium electrode, and as the current density was increased the CE of titanium dissolution was decreased. The titanium dissolution CE showed the maximum value in 0.5 M sulfuric acid and 1.0 M potassium bromide solution. The decrease of titanium electrode CE due to the increase of the electrolysis duration and the AC frequency effect was determined.